A new genus for Cirolana troglexuma Botosaneanu & Iliffe, 1997, an anchialine cave dwelling cirolanid isopod (Crustacea, Isopoda, Cirolanidae) from the Bahamas - Niel L. Bruce; Saskia Brix; Nicholas Balfour; Terue C. Kihara; Alexander M. Weigand; Sevag Mehterian; Thomas M. Iliffe (Subterranean Biology, 2017)
Cirolana troglexuma Botosaneanu & Iliffe, 1997 is redescribed and a Lucayalana Bruce & Brix, gen. n. established for the species. In total 38 specimens were collected from Hatchet Bay Cave, Eleuthera. Specimens on which previous records of L. troglexuma (from Exuma Cays, Cat Island, and Eleuthera) were based have been re-examined when possible. The diagnostic identifying characters and purported apomorphies for Lucayalana gen. n. are: frontal lamina short, narrow, less than 7% width of labrum, not extending to anterior margin of head; pleonite 3 extending posteriorly to posterior of pleonite 5, laterally overlapping pleonites 4 and 5; ventrally broad, forming a strong ventrally directed blade; pereopods 1–3 merus inferior margin RS not molariform. Mitochondrial COI and 16S loci and the nuclear 18S locus data show that all specimens are the one species. Comparison to additional cirolanid COI sequence data (BOLD, GenBank) show that Lucayalana troglexuma is genetically distinct to all other cirolanid genera with available COI sequences. The single male and females have shared COI (with three females), 16S (eight females) and 18S sequences (two females).